Leverage dan Likuiditas pada Opini Audit Going concern Dimoderasi Kualitas Audit - Mariatul Hikmah, Lutfia; Pamungkas, Imang Dapit (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
The company's business continuity can be evaluated from financial documents in the form of financial statements. The phenomenon that occurred, the IDX has sent a letter of reprimand to 129 companies that until April 1, 2024 have not submitted their Annual Audited Financial Statements as of December 31, 2023. The purpose of this study is to obtain factual evidence of the influence of leverage and liquidity on audit opinions, going concerns, moderated audit quality. This type of research is quantitative with secondary data objects for non-primary consumer sector companies in 2021-2023 as many as 309 companies. The analysis technique by model testing uses WarpPLS 7.0 which is based on the Partial Least Squares- Structural Equation Modeling (PLS-SEM) method. The research show that leverage and liquidity have a significant effect on the audit opinion going concern. Audit quality cannot moderate the relationship between leverage and audit opinion going concern. However, audit quality can strengthen the moderation of the relationship between liquidity and audit opinion going concern.